Endometriosis and risk of cardiovascular disease: a systematic review and meta-analysis - Sina Parsa; Rashin Noroozpoor; Hojat Dehghanbanadaki; Sorour Khateri; Yousef Moradi (BMC Public Health)
Abstract Background This systematic review and meta-analysis aimed to evaluate the association between endometriosis and the risk of cardiovascular disease (CVD). Methods A comprehensive literature search was conducted in PubMed (Medline), Scopus, Web of Science, and Embase, covering studies published from January 2000 to April 2023. Cohort and case-control studies investigating the relationship between endometriosis and CVD risk were included. Random-effects or fixed-effects models were used depending on the heterogeneity among studies. Pooled relative risks (RR) with 95% confidence intervals (CIs) were calculated. Study quality was assessed using an appropriate tool, and statistical heterogeneity was evaluated using the I2 statistic. The review was conducted following PRISMA 2020 guidelines. Results Six studies were included in the meta-analysis. Women with endometriosis had a 23% higher risk of developing CVD (RR = 1.23; 95% CI: 1.16–1.31) compared to those without endometriosis. Additionally, the risk of hypertension was 13% higher among women with endometriosis (RR = 1.13; 95% CI: 1.10–1.16). Moderate heterogeneity was observed across studies, and a random-effects model was applied. Conclusion This meta-analysis highlights an increased risk of CVD and hypertension among women with endometriosis. These findings underscore the importance of cardiovascular monitoring and preventive strategies in this population. Trial registration PROSPERO (ID: CRD42023398887).